2015
DOI: 10.1016/j.procs.2015.02.020
|View full text |Cite
|
Sign up to set email alerts
|

Particle Swarm Optimization over Back Propagation Neural Network for Length of Stay Prediction

Abstract: Length of stay of an inpatient reflects the severity of illness as well as the practice patterns of the hospital. Predicting the length of stay will provide a better perception of the different resources consumed in a healthcare system. Neural network trained using back propagation has been discerned as a successful prediction model in healthcare systems 1 . In this paper, a robust stochastic optimization technique called Particle Swarm Optimization (PSO) is compared with back propagation for training. The alg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(21 citation statements)
references
References 10 publications
0
18
0
1
Order By: Relevance
“…38 PSO performs better than BP and GA in terms of rate of concentration. 39,40 According to the above results, we compared our proposed "CLAHE+MGLCM+PSONN" method with the state-of-the-art approaches: NBC, 9 WN+SVM, 10 ELM, 11 and CLAHE+ELM. 12 The results in Table 5 and Figure 8 showed that the "CLAHE+MGLCM+PSONN" method performed the best accuracy of 78.20% in differentiating chronic gingivitis.…”
Section: Discussionmentioning
confidence: 99%
“…38 PSO performs better than BP and GA in terms of rate of concentration. 39,40 According to the above results, we compared our proposed "CLAHE+MGLCM+PSONN" method with the state-of-the-art approaches: NBC, 9 WN+SVM, 10 ELM, 11 and CLAHE+ELM. 12 The results in Table 5 and Figure 8 showed that the "CLAHE+MGLCM+PSONN" method performed the best accuracy of 78.20% in differentiating chronic gingivitis.…”
Section: Discussionmentioning
confidence: 99%
“…A famous training method is the back-propagation (BP) algorithm. However, the previous paper mentioned the accuracy advantage of the NN trained by PSO when compared with the NN trained by BP algorithm [6][7][8][9]. The previous paper proposed a framework for the co-design of the NN trained by PSO algorithm [15][16][17].…”
Section: Neural Network Trained By Standard Psomentioning
confidence: 99%
“…However, the PSO algorithm has shown the advantages in the training of the NN compared with the using of BP to train the NN. The NN trained by the PSO algorithm had obtained higher accuracy concerning the learning error and the recognition rate than the NN trained by conventional BP algorithm [6][7][8][9]. The PSO is the algorithm based on the social behavior of a swarm.…”
Section: Introductionmentioning
confidence: 99%
“…BP network is suitable for establishing the nonlinear relationship between the location information of KPCA extraction and the unknown node coordinates, but it is easy to fall into local minimum, slow convergence rate and poor generalization ability. Particle swarm optimization algorithm based on swarm intelligence does not require with the characteristics information of the problem itself, and can effectively shorten the training time of neural network, so using the PSO algorithm to optimize the BP network to find the optimal weights and thresholds of the network before training [23,24]. Particle velocity and position update rule are expressed as follows.…”
Section: Localization Algorithm Based On Pso-bp Neural Networkmentioning
confidence: 99%